2022
DOI: 10.3390/antiox11061035
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Modulates Glucose, Lipid Peroxidation and Hepatic Metabolism in Streptozotocin-Induced Diabetic Pregnant Rats

Abstract: The consumption of functional foods, such as mushrooms, apparently influences Gestational Diabetes Mellitus (GDM), and brings benefits to maternal-fetal health. Ganoderma lucidum contains a variety of bioactive compounds, such as polysaccharides, proteins and polyphenols that are able to control blood glucose and be used in anti-cancer therapy. We aimed to evaluate the effects of the consumption of Ganoderma lucidum (Gl) on maternal-fetal outcomes in streptozotocin-induced GDM (GDM-STZ). Pregnant rats were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Regarding the safety of medicinal mushrooms, Lentinula edodes , which is also an edible mushroom, was evaluated during the gestational period and, like Ab, induced decreases in the morphological measurements of fetuses (Frizo et al, 2014). Our results are still similar to those of Viroel and collaborators (Viroel et al, 2022), who found an increase in some parameters of fetal measurements after using the Ganoderma lucidum mushroom in pregnant rats. Considering the increase in thoracic measurements, all groups exposed to Pb and Ab showed this alteration.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the safety of medicinal mushrooms, Lentinula edodes , which is also an edible mushroom, was evaluated during the gestational period and, like Ab, induced decreases in the morphological measurements of fetuses (Frizo et al, 2014). Our results are still similar to those of Viroel and collaborators (Viroel et al, 2022), who found an increase in some parameters of fetal measurements after using the Ganoderma lucidum mushroom in pregnant rats. Considering the increase in thoracic measurements, all groups exposed to Pb and Ab showed this alteration.…”
Section: Discussionsupporting
confidence: 92%
“…GLPP is a kind of polysaccharide peptide compound isolated from the fruit body of Ganoderma lucidum, which has long been recognized as a precious Chinese herbal medicine with various biological activities, such as antioxidant stress and anti-inflammatory activities. [63][64][65] In addition, GLPP has a protective effect in various metabolic diseases, such as diabetes mellitus and nonalcoholic fatty liver disease, which is dependent on its regulation of AMPK, the core regulation of metabolic homeostasis. 32,66 Interestingly, inhibition of AMPK by UA has been shown in the liver and kidneys.…”
Section: Papermentioning
confidence: 99%
“…Therefore, Gl can potentially act as a nutritional therapeutic agent for diabetic complications, mainly by regulating glucose metabolism and preventing lipid oxidation without adverse reactions. 119…”
Section: Effects Of Polyphenols On Mothers With Maternal Diabetes And...mentioning
confidence: 99%
“…Therefore, Gl can potentially act as a nutritional therapeutic agent for diabetic complications, mainly by regulating glucose metabolism and preventing lipid oxidation without adverse reactions. 119 Collectively, some polyphenols and Chinese herbal medicines rich in polyphenols exert beneficial effects on insulin and glucose homeostasis in people with GDM. These experiments indicated that polyphenols can alleviate pathological damage to the placenta, liver, pancreas, skeletal muscle, and adipose tissues; reduce inflammation, oxidative stress, and apoptosis; and improve glucose and lipid metabolism and insulin sensitivity, thereby alleviating the symptoms of GDM and improving birth outcomes.…”
Section: Food and Function Reviewmentioning
confidence: 99%